Effects of Qingjin Huatan decoction on pulmonary function and inflammatory mediators in acute exacerbations of chronic obstructive pulmonary disease: a systematic review and meta-analysis - Du, Xuqin; Chen, Yong; Zhang, Ruodai; Shi, Lipeng; Ren, Yi (Frontiers in Pharmacology, 2024)
Background The inflammatory response is the main pathophysiological basis of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) and is a key factor leading to frequent exacerbations and disease progression. Suppressing the inflammatory response can improve pulmonary function, prognosis, and quality of life in AECOPD patients. Purpose To evaluate the effect of Qingjin Huatan decoction (QHD) on pulmonary function and inflammatory mediators in AECOPD patients. Methods Randomized controlled trials (RCTs) on the treatment of AECOPD with QHD were retrieved from eight Chinese and English electronic databases up to 31 May 2024. The quality of the studies was assessed using the Cochrane Risk of Bias Tool and the modified Jadad scale. Statistical analysis, sensitivity analysis, and publication bias assessment were performed using Stata 17.0 software. Results A total of 40 RCTs involving 3,475 AECOPD patients were included. Compared to conventional treatment, QHD significantly improved pulmonary function, with increases in FEV1 (MD = 0.30, 95% CI: 0.26 to 0.34, p = 0.000), FVC (MD = 0.34, 95% CI: 0.27 to 0.41, p = 0.000), FEV1/FVC (MD = 6.07, 95% CI: 5.55 to 6.58, p = 0.000), and PaO2 (MD = 7.20, 95% CI: 4.94 to 9.47, p = 0.000), and a decrease in PaCO2 (MD = −5.37, 95% CI: 7.99 to −2.74, p = 0.000). QHD also significantly suppressed the expression of inflammatory mediators, including TNF-α (MD = −10.87, 95% CI: 12.51 to −9.23, p = 0.000), IL-1β (MD = −13.63, 95% CI: −16.31 to −10.95, p = 0.000), IL-6 (MD = −7.58, 95% CI: −10.10 to −5.06, p = 0.000), IL-8 (MD = −9.45, 95% CI: −12.05 to −6.85, p = 0.000), CRP (MD = −5.62, 95% CI: −6.60 to −4.65, p = 0.000), and PCT (MD = −0.84, 95% CI: −1.07 to −0.62, p = 0.000). Additionally, QHD improved clinical efficacy (RR = 4.16, 95% CI: 3.26 to 5.30, p = 0.000) without increasing the incidence of adverse reactions (RR = 1.04, 95% CI: 0.68 to 1.61, p = 0.000). Conclusion Existing evidence suggests that QHD can significantly improve pulmonary function, suppress the expression of inflammatory mediators, and enhance clinical efficacy in AECOPD patients, with a good safety profile. Given the limitations of this study, more high-quality studies are needed to provide reliable evidence. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=559436, identifier CRD42024559436